الطرق المختلفة لعرض النحت البارز وتأثيرها على أسلوب التشكيل والموضوعات في الحضارة المصرية القديمة - العلاوي، محمد السيد السيد; عاصم، رنوة أحمد; راجح، سالي السيد (الجمعية العربية للحضارة والفنون الإسلامية, 2023)
عند الحديث عن الفنون في الحضارة المصرية القديمة فإن النحت يأتي في المرتبة الأولى فقد كان أعظم عناصر هذه الحضارة؛ فنحن نجد المصري القديم أول من أتقن فن النحت وبرع فيه وقدم إلينا فنا قويا ناضجا في عهد يكاد يكون عهد بداية الحضارات. واختلفت الموضوعات التي تناولها النحت البارز ما بين مواضيع دينيه ومواضيع دنيوية؛ تنوعت بين معتقدات دينيه وأساطير للآلهة ومعارك وحروب أو تجارة وأحداث اجتماعية... الخ ونعرض في هذا البحث الطرق المختلفة لعرض النحت البارز في الحضارة المصرية القديمة وتأثير تلك الطرق على موضوعات النحت وأسلوب التشكيل؛ بداية من الاختلاف بين طريقة عرض وتناول اللوحات الخارجية والداخلية لأي مبنى سواء كان معبد او مقبره وصولا لما نجده من أعمال نحت بارز بعدة طرق مختلفة للعرض بين الأعمدة والتوابيت والأدوات والأثاث؛ فلم يقتصر وجود النحت البارز على المعابد الدينية فقط إلا أننا على سبيل المثال نجد مقابر المصري القديم لا تخلو من أعمال النحت البارز التي تنقل لنا حياة المتوفي وكل التفاصيل حوله. حتى أن التوابيت نفسها يشغلها النحت البارز بطريقة أكثر تحررا من كونه مجرد لوحة على الجدار مقيدة داخل إطار محدد؛ فقد كانت تلك التوابيت بمثابته ساحة عرض جديدة لأعمال النحت البارز. لذا فالنحت البارز عند المصري القديم لم يكن مجرد فن برع فيه إلا أنه كان بمثابة وسيلة التواصل الرئيسية بين الحضارة المصرية القديمة والمستقبل أجمع. When talking about the arts in the ancient Egyptian civilization, the first thing that comes to mind is the art of sculpture, which comes in the first place as it is the greatest element of this civilization; We find the ancient Egyptian to be the first who mastered the art of sculpture and excelled in it and presented to us a solid and mature art in an era that is almost the era of the beginning of civilizations. Sculpture is one of the arts that is characterized by belonging to the heritage. It was used by the ancient civilizations to express their skill and they used relief sculpture to record their history. This is what the ancient Egyptians excelled in, as they presented the relief sculpture in a very precise way in order to immortalize their history and they practiced it on all the walls of their temples to tell us their history and the secret behind the greatness of that ancient civilization. The themes dealt with through relief sculpture varied between religious and secular ones, as they diversified between the expression of religious beliefs, myths of the gods, battles and wars or trade and social events... etc. The presence of relief sculpture was not limited to religious temples only, as we find, for example, that there is hardly a tomb of the ancient Egyptians that does not contain works of relief sculpture that convey to us the life of the deceased and all the details around him, even the coffins themselves are decorated with relief sculpture in a way that is more liberating than being just a panel on the wall confined within a specific frame, as these coffins served as a new exhibition ground for relief sculpture. Therefore, the relief sculpture of the ancient Egyptian was not just an art he mastered, but rather was the main means of communication between the ancient Egyptian civilization and the future as a whole. However, the ancient Egyptian excelled in the art of sculpture and varied between high relief and bas-relief. He was interested in the accuracy of the details and studied the anatomy of humans and animals and laid down his relevant own rules, showing nature from his own perspective.
Keywords: الحضارة المصرية -- فن النحت -- النحت البارز